2009
DOI: 10.1038/onc.2009.84
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide reductase small subunit p53R2 suppresses MEK–ERK activity by binding to ERK kinase 2

Abstract: The p53-dependent RR small subunit (p53R2) protein, a newly identified member of the ribonucleotide reductase family, plays a key role in the p53-dependent cellular response to DNA. Several recent studies have suggested that p53R2 also plays an important role in suppressing the invasive potential of human cancer cells. However, the cellular mechanism that regulates invasiveness remains largely unknown. In this study, we show that p53R2 interacts with MEK2 (extracellular signal-regulated kinase (ERK) kinase 2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…After 24 h, noninvading cells were removed from the upper membrane surface of the insert using a cotton swab. The invading cells on the lower membrane were stained and counted (32). Statistical Analysis-Results are expressed as mean Ϯ S.E.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, noninvading cells were removed from the upper membrane surface of the insert using a cotton swab. The invading cells on the lower membrane were stained and counted (32). Statistical Analysis-Results are expressed as mean Ϯ S.E.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it encodes the regulatory subunit of ribonucleotide reductase which was inhibited by gemcitabine metabolites (5′ diphosphate) 18. In a recent study, ribonucleotide reductase might play a key role in suppressing the invasive capacity and anchorage‐independent growth of human lung cancers through the ability of the ribonucleotide reductase small subunit p53R2 to bind ERK kinase 2, thereby suppressing MEK‐ERK activity 19.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated expression of P53R2 has been shown in various cancer types. 20 P53R2 repairs DNA and acts as scavenger of ROS, maintaining cell survival of both cancerous and non-cancerous cells. Also, other studies showed apposite effects and in some cancers elevated P53R2 level can causes cancer progression through exerting resistance to DNA damaging therapies such as clofarabine and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, P53R2 down-regulates MEK-ERK signal pathway through direct interaction with ERK-Kinase2. 20 MEK-ERK signaling pathway regulates various cellular processes including cell cycle progression and cell survival, thus inhibition of this pathway is another anti-cancer property of P53R2. 21,22 Since the P53R2 is critical molecule in dNTP formation and DNA repair, we hypothesizes that clofarabine might plays a role in apoptosis and cancer therapy by altering the expression levels of P53R2 gene.…”
mentioning
confidence: 99%